Burden of respiratory disease in Thailand: Results from the APBORD observational study. Issue 28 (July 2016) - Thanaviratananich, Sanguansak; Cho, Sang-Heon; Ghoshal, Aloke Gopal; Muttalif, Abdul Razak Bin Abdul; Lin, Horng-Chyuan; Pothirat, Chaicharn; Chuaychoo, Benjamas; Aeumjaturapat, Songklot; Bagga, Shalini; Faruqi, Rab; Sajjan, Shiva; Baidya, Santwona; et al.
Abstract : Abstract: Asia-Pacific Burden of Respiratory Diseases (APBORD) was a cross-sectional, observational study examining the burden of respiratory disease in adults across 6 Asia-Pacific countries. This article reports symptoms, healthcare resource utilization (HCRU), work impairment and cost burden associated with allergic rhinitis (AR), asthma, chronic obstructive pulmonary disease (COPD), and rhinosinusitis in Thailand. Consecutive participants aged ≥18 years with a primary diagnosis of AR, asthma, COPD, or rhinosinusitis were enrolled at 4 hospitals in Thailand during October 2012 and October 2013. Participants completed a survey detailing respiratory symptoms, HCRU, work productivity, and activity impairment. Locally sourced unit costs were used in the calculation of total costs. The study enrolled 1000 patients. The most frequent primary diagnosis was AR (44.2%), followed by rhinosinusitis (24.1%), asthma (23.7%), and COPD (8.0%). Overall, 316 (31.6%) of patients were diagnosed with some combination of the 4 diseases. Blocked nose or congestion (17%) and cough or coughing up phlegm (16%) were the main reasons for the current medical visit. The mean annual cost for patients with a respiratory disease was US$1495 (SD 3133) per patient. Costs associated with work productivity loss were the principal contributor for AR and rhinosinusitis patients while medication costs were the highest contributor for asthma and COPD patients. The study findings highlight the burden associated with 4 prevalent respiratory diseases in Thailand. Thorough investigation of concomitant conditions and improved disease management may help to reduce the burden of these respiratory diseases.